1998
DOI: 10.1063/1.367586
|View full text |Cite
|
Sign up to set email alerts
|

New applications of nanocrystalline Fe(Co–Fe)–Hf–O magnetic films to micromagnetic devices

Abstract: New applications of high resistivity magnetic films, such as Fe–Hf–O and Co–Fe–Hf–O as thin film inductors and flux gate magnetic sensors, were investigated. These soft magnetic films with nanocrystalline structure and high resistivity were deposited on glass substrate by using the oxygen reactive sputtering method. Planar sandwich thin film inductors developed by using Fe–Hf–O or Co–Fe–Hf–O films had a higher quality factor than that of an amorphous Co–Ta–Hf film inductor. The dc–dc converter using the Fe(Co–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 4 publications
0
23
0
Order By: Relevance
“…Hayakawa et al [10] first reported that Fe-M-O (M = Hf, Zr) magnetic films possessed a good magnetic softness owing to their nanostructure which consisted of ferromagnetic bcc nanocrystals (∼10 nm in size) embedded in an amorphous matrix containing large amounts of M and O elements. Soon after this work, several attempts were made to improve the high-frequency performance of these films [11][12][13][14][15][16][17][18][19]. It was found that the addition of Co to Fe-Hf-O films led to a significant improvement in the high-frequency magnetic response, mainly due to an increase in the crystalline anisotropy of the nanograins.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hayakawa et al [10] first reported that Fe-M-O (M = Hf, Zr) magnetic films possessed a good magnetic softness owing to their nanostructure which consisted of ferromagnetic bcc nanocrystals (∼10 nm in size) embedded in an amorphous matrix containing large amounts of M and O elements. Soon after this work, several attempts were made to improve the high-frequency performance of these films [11][12][13][14][15][16][17][18][19]. It was found that the addition of Co to Fe-Hf-O films led to a significant improvement in the high-frequency magnetic response, mainly due to an increase in the crystalline anisotropy of the nanograins.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the addition of Co to Fe-Hf-O films led to a significant improvement in the high-frequency magnetic response, mainly due to an increase in the crystalline anisotropy of the nanograins. Sato et al [11,12] revealed that magnetic inductors using Co-Fe-Hf-O thin films had a higher quality factor and conversion efficiency than those using Fe-Hf-O and Co-Ta-Hf thin films. Since the Co-Fe-Hf-O thin films are insensitive to oxygen at interfaces, they could also be used as free layers for fabrication of spin-dependent tunnelling (SDT) junctions [16] and as electrode layers for tunnelling magnetoresistive (TMR) junction applications [17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prototype microfabricated thin-film magnetic components for power conversion have been reported in [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24]. However, these designs are limited by low efficiency (often 60% or lower), low power density (often under 1 W/cm ¾ of substrate area), or both.…”
Section: Introductionmentioning
confidence: 99%